Determining Symmetry Properties of Gravitational Fields of Terrestrial Group Planets - R.A. Kascheev; I.O. Novlyanskaya (Учёные записки Казанского университета: Серия Естественные науки)
Numerous models of gravity fields of the Solar system bodies have been constructed recently owing to successful space missions. These models are sets of harmonic coefficients of gravity potential expansion in series of spherical functions, which is Laplace series. The sets of coefficients are different in quantity of numerical parameters, sources and composition of the initial observational data, methods to obtain and process them, and, consequently, in a variety of properties and accuracy characteristics. For this reason, the task of comparison of different models of celestial bodies considered in the paper is of interest and relevant. The main purpose of this study is comparison of the models of gravitational potential of the Earth, Moon, Mars, and Venus with the quantitative criteria of different types of symmetries developed by us. It is assumed that some particular symmetry of the density distribution function of the planetary body causes similar symmetry of its gravitational potential. The symmetry of gravitational potential, in its turn, imposes additional conditions (restrictions), which must be satisfied by the harmonic coefficients. The paper deals with seven main types of symmetries: central, axial, two symmetries specular relative to the equatorial planes and prime meridian, as well as three rotational symmetries (at π angle) around the coordinate system axes. According to the results of calculations carried out for the Earth, Moon, Mars, and Venus, the values of the criteria vary considerably for different types of symmetries and for different planets. It means that the specific value of each criterion corresponding to a particular celestial body is indicative of the properties and internal structure characteristics of the latter and, therefore, it can be used as a tool for comparative planetology. On the basis of the performed calculations, it is possible to distinguish two groups of celestial bodies having similar properties of axial, specular, and rotational planetary symmetries: the Venus and Earth are more symmetrical, while the Moon and Mars are less symmetrical.